2021
DOI: 10.1111/cod.13966
|View full text |Cite
|
Sign up to set email alerts
|

Facial contact dermatitis caused by cosmetic‐relevant allergens

Abstract: Background: Facial allergic contact dermatitis caused by cosmetic products is common. New allergens in cosmetics continuously emerge.Objectives: To investigate characteristics of patients with facial dermatitis (FD) between 2010 and 2019 including patch test results from cosmetic-related allergens and a new test series with cosmetic-relevant natural ingredients (CRNIs).Methods: This is a retrospective study analysing demographics, clinical characteristics according to MOAHLFA index (male; occupation; atopic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
(97 reference statements)
0
7
1
Order By: Relevance
“…Nowadays, also due to the availability of the commercial test preparations, increasing numbers of cases of sensitization to Lim-OOHs and Lin-OOHs have been described when studying contact allergy to cosmetics, (eg on the face). 36 In addition, early and continuous exposure to Lim-OOHs and Lin-OOHs may have an impact on children. A Belgian study demonstrated that the most frequent sensitizations in 329 children patch tested from 2010 to 2019 were to nickel sulfate and Lin-OOHs (both 16%), Lim-OOHs (13.5%) and paraphenylenediamine (10.9%).…”
Section: Past Studies Of Experience From Patch Testing With Lim-oohs ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, also due to the availability of the commercial test preparations, increasing numbers of cases of sensitization to Lim-OOHs and Lin-OOHs have been described when studying contact allergy to cosmetics, (eg on the face). 36 In addition, early and continuous exposure to Lim-OOHs and Lin-OOHs may have an impact on children. A Belgian study demonstrated that the most frequent sensitizations in 329 children patch tested from 2010 to 2019 were to nickel sulfate and Lin-OOHs (both 16%), Lim-OOHs (13.5%) and paraphenylenediamine (10.9%).…”
Section: Past Studies Of Experience From Patch Testing With Lim-oohs ...mentioning
confidence: 99%
“…Nowadays, also due to the availability of the commercial test preparations, increasing numbers of cases of sensitization to Lim‐OOHs and Lin‐OOHs have been described when studying contact allergy to cosmetics, (eg on the face) 36 . In addition, early and continuous exposure to Lim‐OOHs and Lin‐OOHs may have an impact on children.…”
Section: Current Knowledge About the Sensitizing Capacity And The Dia...mentioning
confidence: 99%
“…The SCP samples contained three facial toners, six facial essences, six facial creams, four body lotions, and three hand moisturizers. The HCP samples included eight hair dyes, and the RG samples were made of latex (13), nitrile (4), and polyvinyl chloride (1).…”
Section: Sample Collection Four Categories Of Samples 29mentioning
confidence: 99%
“…Research on daily used products, like wearable products, remained insufficient, although a few clinical records on contact urticaria characterized by the presence of a rash focally under watch bands was occasionally reported . Currently available data on skin allergy from usage of commodities were mostly based on epidemiological studies or individual medical record. , The traditional patch testing was a major approach for finding suspicious allergens with a complex matrix, , which was unfavorable or unable to meet the requirement for the efficient prediction of skin sensitization potency of commodities. Screening skin allergy potential for all sorts of skin-contact products using an in vitro high-throughput assay was thus necessary.…”
Section: Introductionmentioning
confidence: 99%
“…13 Many naturally derived ingredients are the cause of dermatitis, with the most common cosmetic-related natural ingredients causing facial dermatitis being propolis and hydroperoxides of limonene and linalool. 14 Our role is to educate about misinformation and marketing strategies to direct patients towards safe, effective, and affordable skincare. Patients should be encouraged to investigate how the terms clean, natural, organic, vegan, and cruelty-free are defined by the producers of their personal care products.…”
mentioning
confidence: 99%